2015
DOI: 10.7196/samjnew.7919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic accuracy of the HemoCue device for detecting anaemia in healthy school- aged children in KwaZulu-Natal, South Africa

Abstract: Anaemia frequently occurs in association with an underlying condition and is linked to poor clinical outcomes. In school-aged children in sub-Saharan Africa, the prevalence of anaemia is reported to be high (affecting 25.4%). [1] There is, however, a notable paucity of data relating to haemoglobin (Hb) levels, onset and duration of anaemia, and the underlying illness causing the anaemia in schoolaged children. This is a significant deficiency, as any anaemia, even if it is mild, can compromise growth and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
14
1
3
Order By: Relevance
“…Third, most of variables measured in the study were self-reported, which make the results of study subject to recall and social desirability biases. Fourth, measuring serum haemoglobin concentration at the population level as an indicator of anaemia is considered the most reliable method as compared to other clinical measures (39,40). However, anaemia is a multifaceted condition that requires obtaining medical and family histories as well as physical examination for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, most of variables measured in the study were self-reported, which make the results of study subject to recall and social desirability biases. Fourth, measuring serum haemoglobin concentration at the population level as an indicator of anaemia is considered the most reliable method as compared to other clinical measures (39,40). However, anaemia is a multifaceted condition that requires obtaining medical and family histories as well as physical examination for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that capillary Hb concentrations by HemoCue Hb301 are significantly higher than venous Hb concentrations obtained with two different automated haematology analysers is consistent with some previous studies in pregnant women in Sudan 19 and Brazil, 36 blood donors in the USA 26 and different population subgroups (preschool children, school children, pregnant women, non-pregnant women and men) in Ghana, 25 but not with studies in women with genetic Hb disorders in Cambodia, 21 adults and children in Mexico, 29 blood donors in Ireland 38 and children in South Africa. 30 Time and position during blood collection 39 40 have been suggested to explain discrepancies between different devices and to influence the variability in Hb levels obtained by HemoCue. An additional source of error may be inadequate mixing of venous blood in the blood collection tube, which may lead to a reading of relatively more plasma rather than red blood cells by the automated analyser and would result in a lower Hb concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies analyzed venous blood with eight comparisons finding higher mean Hb concentrations (2.0−16.0 g/L) by the Hb-201+ compared with the reference 8,19,54,103,104,106,107,139 and four comparisons found lower mean Hb concentrations (0.2−15.0 g/L). 64,115,147 Fourteen comparisons from 13 studies compared capillary blood with venous blood 8,54,64,65,103,[108][109][110][111][112][113][114]133 with 9 comparisons finding higher mean Hb concentrations (2.0−9.0 g/L). 8,54,103,108,[110][111][112][113] Five found a lower mean Hb concentration (2.6−13.0 g/L for all findings).…”
Section: Comparability Of the Automated Hematology Analyzer With Hemomentioning
confidence: 99%
“…8,54,103,108,[110][111][112][113] Five found a lower mean Hb concentration (2.6−13.0 g/L for all findings). 64,65,109,114,115 When applying the mean concentration variation threshold of ±7% for the studies comparing the Hb-201+ with the reference, 27 of the 28 comparisons 8,19,54,64,65,104,[106][107][108][109][110][111][112][113][114]133,139,147 met the allowable degree of variation with one comparison from one study exceeding the ±7% bias 115 (Fig. 3A).…”
Section: Comparability Of the Automated Hematology Analyzer With Hemomentioning
confidence: 99%